3x+(-11y)+(-12x)+7y=

Simple and best practice solution for 3x+(-11y)+(-12x)+7y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+(-11y)+(-12x)+7y= equation:


Simplifying
3x + (-11y) + (-12x) + 7y = 0

Reorder the terms:
3x + (-12x) + (-11y) + 7y = 0

Combine like terms: 3x + (-12x) = -9x
-9x + (-11y) + 7y = 0

Combine like terms: (-11y) + 7y = -4y
-9x + -4y = 0

Solving
-9x + -4y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4y' to each side of the equation.
-9x + -4y + 4y = 0 + 4y

Combine like terms: -4y + 4y = 0
-9x + 0 = 0 + 4y
-9x = 0 + 4y
Remove the zero:
-9x = 4y

Divide each side by '-9'.
x = -0.4444444444y

Simplifying
x = -0.4444444444y

See similar equations:

| 18y-21y= | | 6n+7=14 | | x+3x(9)=40 | | 18a=4a-4(a+3) | | 5-7x+6+5x+3x-3=5+2*5 | | 5(3a-1)=-95 | | 2.6x+18=24+22 | | 2.6x+18=24 | | -2m+13=-3 | | 7-9(5x)=20 | | -3(-5k-6)=108 | | 4x*7=49 | | h(t)=1.86t^2+4t-1.86 | | 6+2x=20x | | 6+2x=18x | | -104=4(5p-6) | | 4(x-2)-(2x-5)= | | 4-v+2v=8 | | 3(5+2x)=2x | | 2x=3(5+6x) | | 2b-b+5b=4a | | (-4+xyz)-(5+xyz)= | | 8x=4x-24 | | (7x+2y)+(-3y+x)= | | 4.9*x^2-13*x-23=0 | | 7y=6y-8 | | 3.01i-1.52i= | | p-30=6(h-6) | | -79h-(-9h)= | | -79h-(-9)= | | 5m=4m+7 | | 8x^3-24x^2+18x= |

Equations solver categories